Breslow Intermediates from Aromatic N‐Heterocyclic Carbenes (Benzimidazolin‐2‐ylidenes, Thiazolin‐2‐ylidenes). Issue 27 (7th June 2018) - Paul, Mathias; Sudkaow, Panyapon; Wessels, Alina; Schlörer, Nils E.; Neudörfl, Jörg‐M.; Berkessel, Albrecht
Abstract: We report the first generation and characterization of elusive Breslow intermediates derived from aromatic N‐heterocyclic carbenes (NHCs), namely benzimidazolin‐2‐ylidenes (NMR, X‐ray analysis) and thiazolin‐2‐ylidenes (NMR). In the former case, the diamino enols were generated by reaction of the free N, N‐bis(2, 6‐diisopropylphenyl)‐ and N, N‐bis(mesityl)‐substituted benzimidazolin‐2‐ylidenes with aldehydes while the dimer of 3, 4, 5‐trimethylthiazolin‐2‐ylidene served as the starting material in the latter case. The unambiguous NMR identification of the first thiazolin‐2‐ylidene‐based Breslow intermediate rests on double 13 C labeling of both the NHC and the aldehyde component. The acyl anion reactivity was confirmed by benzoin formation with excess aldehyde. Abstract : The key to carbene‐catalyzed umpolung may be seen in the generation and characterization of Breslow intermediates derived from aromatic N‐heterocyclic carbenes, ideally thiazol‐2‐ylidenes, as in vitamin B1 . The first preparation and characterization of Breslow intermediates from aldehydes and a thiazolin‐2‐ylidene (A ; NMR analysis), as well as benzimidazolin‐2‐ylidenes (B ; NMR, X‐ray analysis), is reported.